Time‐calibrated relationships of a rare cave catfish ( Trichomycterus rubbioli ): Shedding light on troglobitic lifestyle origin in the Brazilian caatinga - Wilson J. E. M. Costa; Paulo J. Vilardo; José Leonardo O. Mattos; Axel M. Katz; Valter M. Azevedo‐Santos; Pedro L. C. Uzeda; Rodrigo L. Ferreira (Journal of Fish Biology, 2026)
Catfishes of the subfamily Trichomycterinae comprise the most diverse fish group with species adapted to live in Neotropical caves, but past evolutionary scenarios that have driven the origin of these troglobitic species remain unknown. We herein investigate the phylogenetic position of the cave‐restricted Trichomycterus rubbioli , endemic to the semi‐arid Caatinga of northeastern Brazil, through a time‐calibrated molecular phylogenetic analysis of a broad sample of trichomycterine taxa (84 spp), using two nuclear and two mitochondrial genes (3030 bp). The analysis supported T. rubbioli as a member of the Trichomycterus s.s. clade endemic to eastern South America and an early Miocene origin for the T. rubbioli lineage. The combination of available data suggests that the T. rubbioli lineage adapted to the troglobitic lifestyle between the Middle and Late Miocene, a period when the semi‐arid conditions of the Caatinga biome became established and consequently streams of the region became seasonal. This past scenario would be responsible for extinction of epigean trichomycterines while preserving the lineage within the cave system. Morphological characters of the troglobitic ‘Trichomycterus’ itacarambiensis from the transition area between the Cerrado and the Caatinga indicate distant relationships with T. rubbioli , suggesting an independent evolutionary event of cave colonization.

Collagen and collagenases in mare’s endometrium with endometrosis - Luiz Augusto M. Centeno; Henrique B.A. Bastos; Verônica L.C. Bueno; Janislene M. Trentin; MarianiF. Fiorenza; Welden Panziera; Gustavo H.Z. Winter; Nelson A. Kretzmann; Sandra Fiala-Rechsteiner; Rodrigo C. Mattos; Mara I.B. Rubin (Theriogenology, 2024)

Stomatal conductance models in Brazilian forest plantations: genotype and environmental effects on eucalypt and pine forests - Juscelina Arcanjo dos Santos; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Ana Helíosa C. Marrichi; Rafaela Lorenzato Carneiro; Paulo Henrique Muller da Silva; Eduardo Moré de Mattos; Marina Shinkai Gentil Otto; Beatriz Teixeira Gonsalez (New Forests, 2024)

Equine endometrial Th1 and Th2 evaluation during early pregnancy - Gustavo R Larentis; Henrique B A Bastos; Giovani C Camozzato; Maria N Martinez; Luiz A M Centeno; Verônica L C Bueno; Gustavo H Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

Evaluation of different platelet-rich plasma protocols for use in the equine reproductive clinic - Joel N De Oliveira; Henrique Ba Bastos; Veronica LC Bueno; Gustavo R Larentis; Rodrigo C Mattos; Adriana P Neves (Journal of Equine Veterinary Science, 2023)

Endometrial fibrosis in mares: Picrosirius Red and Collagen-2 and 3 - Luiz Augusto M Centeno; Henrique BA Bastos; Verônica LC Bueno; Janislene M Trentin; Gustavo R Larentis; Mariani F Fiorenza; Welden Panziera; Gustavo Henrique Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos; Mara Iolanda B Rubin (Journal of Equine Veterinary Science, 2023)

Proteomic profile of stallion seminal plasma - Sandra Fiala-Rechsteiner; Veronica LC Bueno; Edvaldo Barros; Camilo JR López; Pedro MP Vidigal; Humberto JO Ramos; Henrique BA Bastos; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

Metabolomics profile of equine seminal plasma - Veronica LC Bueno; Henrique BA Bastos; Gustavo R Larentis; Gustavo HZ Winter; Rodrigo C Mattos; Sandra Mara E Rechsteiner (Journal of Equine Veterinary Science, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Absorption of 15NH3 volatilized from urea by Citrus trees - Rodrigo M. Boaretto; Dirceu Mattos; José A. Quaggio; Heitor Cantarella; Paulo C. O. Trivelin (Plant and Soil, 2013)

Contribution of phosphorus (32P) absorption and remobilization for citrus growth - Fernando C. Bachiega Zambrosi; Dirceu Mattos; Rodrigo M. Boaretto; José A. Quaggio; Takashi Muraoka; James P. Syvertsen (Plant and Soil, 2012)